Incorporating circularity, sustainability, and systems thinking into an assessment framework for transformative food system innovation - Moores, Alexander; Charalampopoulos, Dimitris; Williams, Adrian; Schmidt Rivera, Ximena (Frontiers in Sustainable Food Systems, 2025)
The transition towards a circular economy in the food system is posited as way to harmonize the provision safe, ample and accessible food to a growing population with the reduction the food system’s widespread impact on natural resources, the environment, and human health. Within the context of circular food innovation, there is an abundance of assessment approaches allowing researchers to evaluate and guide new technologies, applications, and products. However, specialist circularity tools are underutilized. This research draws from wider circular economy discourse, sustainability assessment methods, and systems-transitions theory to propose a novel framework to appraise and guide circular food innovation. Through a systematic literature review and critical analysis, this work highlights the limitations of existing methods based on a multi-disciplinary lens. In lieu of robust circularity metrics, elaborations within the Life Cycle Assessment (LCA) methodology provide a comprehensive sustainability and circularity assessment, while cross-disciplinary approaches inform the development of technological trajectories in line with system-transitions theories. The proposed framework aims to bridge this gap by providing a holistic approach that incorporates systems perspectives and considers the wider dynamics of sustainability and circular economy via future scenario modelling. By integrating these perspectives, the framework facilitates earlier intervention and broader stakeholder engagement in the sustainability assessment process. Examined primarily within the context of food manufacturing, this work provides new tools for academic research and industrial practitioners, driving transformative change towards a more sustainable and circular food system.